EARTH HOUR DARI WWF SEBAGAI SIMBOL GLOBAL MOVEMENT TERHADAP PERUBAHAN IKLIM DUNIA OLEH INGO - Kannaby, Ahmad Haibat; Saadah, Kholifatus (Global and Policy Journal of International Relations, 2018)
This paper focuses on the efforts of the International Non-Gorvernmental Organization (INGO) in overcoming the environmental problems exist in the world. Nowadays, the environmental aspect has received less attention from the state and International Governmental Organization (IGO), this happens because many restrictions owned by one country to other countries are sometimes different in addressing environmental problems. Countries also have different interests in harnessing energy that contributes to environmental damage such as fossil fuels and coal. Renewable energy is considered as expensive and unfavorable technology in terms of financial. The presence of INGO as international relations actor who sees that environmental and natural sustainability is something that is crucial and must be maintained properly, so INGO continuously takes the place in the programs which can create public awareness that the environment must be prioritized. Princen & Finger (1994) explains that there are three things that make INGOs can change the roles related to environmental problems, first is from the institution and the strength of the international structure to the process, the second is from education to strategic interaction, and the last is from the reactive function of INGO to INGO's transformative effects in the global political economy. Keywords: global movement, environment, energy, public awareness, INGODOI: https://doi.org/10.33005/jgp.v6i02.1820